Impact of Rice Husk Ash on the Compaction Characteristics of Soil (Jagannath University Journal of Science, 2024)
Usually, the measurement of maximum dry density (MDD) and optimum moisture content (OMC) is important for assessing the quality control of the compacted fill or earthwork constructions as the compaction parameters. Rice husk ash (RHA), plentifully available in many rice-producing countries, can be used as a building material. This study mainly tries to investigate the effect of RHA on compaction features of sandy soil classified as A-2-4 or SM for soil stabilization. Nominal to a maximal dosage of RHA addition in the soil was considered for the experiments by the standard Proctor compaction tests. The result revealed that by increasing the amount of RHA in the soil, MDD was reduced and OMC increased significantly. It can be concluded that applying a soil-RHA combination is beneficial to soil improvement.Jagannath University Journal of Science, Volume 10, Number II, Dec. 2023, pp. 87-93